Retrospective prevalence of snakebites from Hospital Kuala Lumpur (HKL)(1999-2003) - Jamaiah, I.; Rohela, M.; Ng, T.K.; Ch'ng, K.B.; Teh, Y.S.; Nurulhuda, A.L.; Suhaili, N. (2006)
A hospital based retrospective study of the prevalence of snakebite cases at Hospital Kuala Lumpur was carried out over a five-year period from 1999 to 2003. A total of 126 snakebite cases were recorded. The highest admission for snakebites was recorded in 2001 (29 cases). The majority of cases were admitted for three days or less (79). Most of the snakebite cases were reported in the 11-30 years age group (52). The male:female ratio was 3:1. The majority of cases were Malaysians (80, 101 cases). Of the non-Malaysians, Indonesians constituted the most (56, 14 cases). Bites occurred most commonly on the lower limbs (49), followed by upper limbs (45) and on other parts of the body (6). No fatal cases were detected and complications were scarce. In 60 (70 cases) the snake could not be identified. Of the four species of snakes that were identified, cobra (both suspected and confirmed) constituted the largest group (25), followed by viper (10), python (4) and sea snake (1). The most common clinical presentations were pain and swelling, 92 (116 cases). All patients were put on snakebite charts and their vital signs were monitored. Of the snakebite cases, 48 (61 cases) were treated with cloxacillin and 25 (32 cases) were given polyvalent snake antivenom.